2018
DOI: 10.1002/pon.4962
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' attitudes towards psycho‐oncology, perceived barriers, and psychosocial competencies: Indicators of successful implementation of adjunctive psycho‐oncological care?

Abstract: Objective: Clinical experience reveals a gap between recommended psychosocial care and actual support for psycho-oncology. Physicians are essential for managing psychosocial distress and for the successful implementation of psycho-oncology.The aim was to explore physician's attitudes towards psycho-oncology, their selfperceived barriers towards referral to psycho-oncology, and their personal psychosocial competencies in a maximum-care hospital. Method: Semistructured interviews informed the development of a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Such courses could be offered on a population level as well as in a group with an increased risk of mental health problems (like cancer patients). As we also found that social norms influence positive attitudes, medical staff need to be trained in psychosocial competencies, as recently stressed (Senf, Fettel, Demmerle, & Maiwurm, ). In order to enhance positive attitudes effectively and permanently, it is therefore recommended to combine individual interventions for high‐distressed patients (e.g.…”
Section: Discussionsupporting
confidence: 71%
“…Such courses could be offered on a population level as well as in a group with an increased risk of mental health problems (like cancer patients). As we also found that social norms influence positive attitudes, medical staff need to be trained in psychosocial competencies, as recently stressed (Senf, Fettel, Demmerle, & Maiwurm, ). In order to enhance positive attitudes effectively and permanently, it is therefore recommended to combine individual interventions for high‐distressed patients (e.g.…”
Section: Discussionsupporting
confidence: 71%
“…Frey Nascimento et al found that additional information from a physician about psychological support did not play a role in uptake behavior whereas oncologists' recommendations for psycho‐oncological services were associated with increased uptake of these services. Similarly, Senf et al reported that physicians' personal commitment towards psycho‐oncology influences integration of psycho‐oncology in patient treatment. Thus, physicians' attitude and opinion towards psycho‐oncological care might be a key factor of patients' desire for psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Even using the same assessment, individuals respond in different ways according to the professional undertaking the assessment [5], suggesting that there is no such thing as a 'value free' assessment of holistic need. Consequently, while policy has recognised the importance of routine, person-centred, psychosocial care [6], concerns relating to implementation barriers, the lack of clarity on the best way to identify needs and poor evidence of impact prevents widespread uptake [7,8]. Nevertheless, successful interventions exist.…”
Section: Introductionmentioning
confidence: 99%